HUBUNGAN INTENSITAS MEROKOK ORANG TUA DI DALAM RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS MEDAN DENAI TAHUN 2023 - Fithri Handayani Lubis; Fithri Handayani Lubis (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
One of the behaviors that can cause ISPA is smoking. Smoking does not only threaten someone who smokes but also those around them or passive smokers. Houses where there are families who have smoking habits have the opportunity to increase the incidence of ARI by 7.83 times compared to houses where there are no smoking families in the house. The type of research used is quantitative research with a cross-sectional research design that aims to analyze differences in the incidence of ISPA under five in parents who smoke in the house and parents who don't smoke. The time of the research started from April to June 2023. The population in this study were all families who had toddlers in the working area of the Puskesmas Medan Denai, namely 325 families and based on the Slovin formula, a minimum sample size of 77 respondents was obtained. Based on research and discussion it is known that the majority of respondents have toddlers aged under five (> 2 years-3 years) and have toddlers with female sex, the majority of parents of toddlers have an intensity of smoking 11-20 cigarettes per day and the majority of toddlers who are respondents in the study This patient is not suffering from ISPA and there is a statistical relationship between the Intensity of Parental Smoking in the House and the Incidence of ISPA in Toddlers. As seen from the results of statistical tests conducted using Pearson Chi-Square, p-value = 0.026 (p <α). It is hoped that the Management of the Puskesmas Medan Denai can improve education or outreach programs for families who have smoking habits in the home regarding the health impacts that can be experienced by family members due to smoking behavior and the community in the working area of the Puskesmas Medan Denai, especially those with toddlers. smoking inside the house to avoid the health effects in the form of ISPA conditions in toddlers.